Sosialisasi mikrobiota mulut dan praktik menyikat gigi melalui video edukasi kesehatan untuk mencegah disbiosis oral pada siswa SMP - Juniati Binti Lukman; Ade Irma; Nur Insani Amir (Penamas: Journal of Community Service, 2026)
Oral health among junior high school students remains a public health issue in Indonesia. The main problems faced are students' low knowledge of oral microbiota and inadequate toothbrushing techniques. This community service activity aims to improve junior high school students' knowledge and skills regarding oral microbiota and proper toothbrushing techniques. The method used was a one-day community education program held at the UPTD of SMP Negeri 10 Barru, Barru Regency, South Sulawesi, with 40 eighth-grade students participating. The series of activities included a pre-test, a PowerPoint presentation, educational videos on the Fones toothbrushing method, direct toothbrushing practice with assistance, and a post-test. The instruments used were a knowledge questionnaire (15 multiple-choice questions) and a skills observation sheet (7 criteria). The results of this activity showed an increase in students' knowledge and skills in proper toothbrushing. The conclusions from this activity can be recommended for regular implementation in other schools as a structured oral health program.